Uvajanje rešitev ERP v slovenskih podjetjih - Sternad Zabukovšek, Simona (Organizacija (Kranj), 2008)
A lot of Slovenian companies decided to implement enterprise resource planning (ERP) solutions in the past several years. Published articles on theme ERP implementation had shown that some critical success factors (CSF) of such implementation have significant influence on successfulness of implementation of ERP solutions. These factors are: top management support and involvement, clear goals, objectives and scope, project team competence and organization, user training and education, business process reengineering, change management, effective communication, user involvement, data analysis and conversion, consultants, project management, project champion, architecture choice (package selection) and minimal customization and some less important factors. To research the importance of ERP implementation CSFin Slovenian companies which had implemented SAP R/3 or mySAP ERP, Microsoft Navision and GEAC System, an empirical study in 206 Slovenian companies has been conducted. Our research has verified more hypotheses, which we were set up on the bases of preliminary research. In this article we are going to focus on three hypotheses, which were verified. On the basis of research we can confirm our hypothesis: there are no differences of ranking ERP implementation CSF between Slovenia and abroad, there are groups of relations ERP implementation CSF where inside them are no bigger statistical differences and that there are links between ERP implementation CSF.
Keywords: podjetja; elektronsko poslovanje; informacijska tehnologija; information technology; informatika; information science; informacijski sistemi; računalniška programska oprema; planiranje; Slovenia; Slovenija